2017
DOI: 10.1164/rccm.201604-0761oc
|View full text |Cite
|
Sign up to set email alerts
|

Resonance as the Mechanism of Daytime Periodic Breathing in Patients with Heart Failure

Abstract: Rationale: In patients with chronic heart failure, daytime oscillatory breathing at rest is associated with a high risk of mortality. Experimental evidence, including exaggerated ventilatory responses to CO 2 and prolonged circulation time, implicates the ventilatory control system and suggests feedback instability (loop gain . 1) is responsible. However, daytime oscillatory patterns often appear remarkably irregular versus classic instability (Cheyne-Stokes respiration), suggesting our mechanistic understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Fourier transform analysis of ventilation and P ETC O2 changes at this frequency described controller (Δventilation/ΔP ETC O2) and plant gains (ΔP ETC O2/Δventilation*; *ventilation, corrected for inspired PnormalCO2, yields a ventilatory disturbance (Ghazanshahi & Khoo, ; Sands et al . ) as shown in Figs and (red dashed lines)). Overall loop gain equals controller × plant (Ghazanshahi & Khoo, ; Sands et al .…”
Section: Methodssupporting
confidence: 51%
See 3 more Smart Citations
“…Fourier transform analysis of ventilation and P ETC O2 changes at this frequency described controller (Δventilation/ΔP ETC O2) and plant gains (ΔP ETC O2/Δventilation*; *ventilation, corrected for inspired PnormalCO2, yields a ventilatory disturbance (Ghazanshahi & Khoo, ; Sands et al . ) as shown in Figs and (red dashed lines)). Overall loop gain equals controller × plant (Ghazanshahi & Khoo, ; Sands et al .…”
Section: Methodssupporting
confidence: 51%
“…), a modification of the pseudo‐random binary stimulation approach (Ghazanshahi & Khoo, ; Sands et al . ). A gas mixture (6% CO 2 –14% O 2 ) was chosen to mimic alveolar gases and thereby simulate apnoea without disturbing the participant.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…20) According to a combination of mathematical modeling and direct measurement, daytime oscillatory breathing in heart failure is closely related to chemoreflex hypersensitivity and reduced stability that predicts mortality in patients with advanced heart failure. 21) Himi, et al concluded that cardiac function is more impaired in cardiac patients who manifest oscillatory breathing at rest and during exercise than in those who manifest oscillatory breathing only at rest or only during exercise. 20) The frequent occurrence of oscillatory breathing may be a more important indicator for severe heart failure, regardless of during exercise or at rest.…”
Section: Article P 713mentioning
confidence: 99%